Conditional knockout of C/EBPβ in epidermis results in dysregulated lipid biosynthesis and a defect in skin barrier function - Kevin J. Mills; Michael Doyle; John S. House; John G. Witherspoon; Daniel Krakko; Whitney L. Stutts; Jessie R. Chappel; Jonathan R. Hall; Erin S. Baker; Robert C. Smart (PLoS ONE, 2025)
CCAAT/enhancer binding protein-β (C/EBPβ) is a basic leucine zipper transcription factor that is abundantly expressed in epidermal keratinocytes of skin. In the present study, C/EBPβ epidermal specific conditional knockout (CKOβ) SKH1 mice were utilized to interrogate C/EBPβ’s role in lipid biosynthesis and skin barrier integrity. RNAseq data analysis and gene set enrichment analysis of RNA isolated from the epidermis of CKOβ and K5Cre control mice revealed that deletion of C/EBPβ in epidermis resulted in an enrichment of downregulated genes in gene sets associated with lipid metabolism. Further analysis showed the majority of differentially regulated genes were downregulated in gene sets related to the metabolism/biosynthesis of ceramides, fatty acids, phospholipids, sphingolipids, and cholesterol species in CKOβ epidermis. Ingenuity Pathway Analysis predicted inhibition of multiple pathways involving lipid biosynthesis. Lipidomic analysis of epidermis using advanced chemical separations and tandem mass spectrometry identified 470 individual lipids in epidermis with 165 significantly decreased and 82 significantly increased in CKOβ epidermis. The lysophospholipids were the most decreased class of lipids, and free fatty acids and ceramides important in barrier formation were also decreased. The sphingomyelin class of lipids was the most increased. High resolution mass spectrometry for cholesterol lipids revealed several cholesterol esters were also dysregulated in CKOβ epidermis. Finally, we assessed the functional consequences of the loss C/EBPβ on epidermal barrier function and found that basal permeability barrier function as measured by transepidermal water loss (TEWL) was impaired, with an approximate doubling of TEWL in CKOβ mice. These results indicate that C/EBPβ is a is a major regulator of the epidermal lipidome and the deletion of C/EBPβ in epidermis leads to a defect in skin barrier function.